2010
DOI: 10.1021/ie901060e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuO Nanoparticles in Enhancing the Thermal Conductivities of Monoethylene Glycol and Paraffin Fluids

Abstract: The effect of CuO nanoparticles on the thermal conductivities of paraffin and monoethylene glycol (MEG) was investigated. An enhancement in the effective thermal conductivity was found for both fluids. This enhancement was studied with regard to various factors: nanoparticle concentration, nanoparticle size, and base-fluid type. For both base fluids, an improvement in thermal conductivity was found as nanoparticle concentration increased; this was attributed to an increase in particle-to-particle interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Fig. 9 Comparison with previously reported work and our proposed work on temperature-dependent nanofluid thermal conductivity ratio for alumina nanofluid (Maxwell 1954;Hamilton and Crosser 1962;Wang et al 2008;Beck et al 2009;Moghadassi et al 2010;Kleinstreuer and Feng 2011;Chon et al 2005;Li and Peterson 2006) Due to the particle volume concentration the dynamic viscosity of nanofluid has been increased and as temperature increases viscosity decreases, which is concluded by Nguyen et al (Nguyen et al 2008;Chandrasekar et al 2010). This process is the witness for the particle suspension beyond the critical temperature, which caused by the hysteresis phenomenon.…”
Section: Effective Viscosity Of Nanofluidsupporting
confidence: 65%
See 1 more Smart Citation
“…Fig. 9 Comparison with previously reported work and our proposed work on temperature-dependent nanofluid thermal conductivity ratio for alumina nanofluid (Maxwell 1954;Hamilton and Crosser 1962;Wang et al 2008;Beck et al 2009;Moghadassi et al 2010;Kleinstreuer and Feng 2011;Chon et al 2005;Li and Peterson 2006) Due to the particle volume concentration the dynamic viscosity of nanofluid has been increased and as temperature increases viscosity decreases, which is concluded by Nguyen et al (Nguyen et al 2008;Chandrasekar et al 2010). This process is the witness for the particle suspension beyond the critical temperature, which caused by the hysteresis phenomenon.…”
Section: Effective Viscosity Of Nanofluidsupporting
confidence: 65%
“…Basic classical models are mainly giving conclusions regarding particle size, shape, concentration, which helps to assume heat transfer in particles as well as in fluid (Wang et al 2008). Beck et al (2009) and Moghadassi et al (2010) observed that the thermal conductivity will upgrade with the decreasing of nanoparticle size. Kleinstreuer and Feng (2011) established relationship between thermal conductivity and some fundamental parameters like concentration, temperature, particle size which are exceptionally valuable for a nanofluid.…”
Section: Thermal Conductivity Of Nanofluidmentioning
confidence: 99%
“…As the thickness of the interfacial shell increases, there is a corresponding increase in the volume of the interface, which results in greater heat conduction. [26] The viscosity of the fluid and the interfacial thickness of the particle-fluid interface affect the thermal conductivity of nanofluids.…”
Section: Effect Of Base Fluidsmentioning
confidence: 99%
“…Therefore, overall heat transfer coefficient and then heat transfer rate increases (Eqs. (5) and (6)). Figs.…”
Section: Effect Of the Mass Flow Rate On Heat Transfer Performancementioning
confidence: 99%
“…Nanofluids are stable suspension of the nanoparticles in a base fluid like water, ethylene glycol and industrial oils. Nanoparticles can be metallic like Silver [1] and Copper [2], metal oxide like Al 2 O 3 [3] and CuO [4,5] and nonmetallic like SiC [6] and carbon nanotubes (CNT) [7,8]. Nanofluids containing nanoparticles exhibit enhanced the heat transfer characteristics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%